Assessing current genetic status of the Hainan gibbon using historical and demographic baselines: implications for conservation management of species of extreme rarity. Issue 15 (9th July 2016) - Bryant, J. V.; Gottelli, D.; Zeng, X.; Hong, X.; Chan, B. P. L.; Fellowes, J. R.; Zhang, Y.; Luo, J.; Durrant, C.; Geissmann, T.; Chatterjee, H. J.; Turvey, S. T.
Abstract: Evidence‐based conservation planning is crucial for informing management decisions for species of extreme rarity, but collection of robust data on genetic status or other parameters can be extremely challenging for such species. The Hainan gibbon, possibly the world's rarest mammal, consists of a single population of ~25 individuals restricted to one protected area on Hainan Island, China, and has persisted for over 30 years at exceptionally low population size. Analysis of genotypes at 11 microsatellite loci from faecal samples for 36% of the current global population and tissue samples from 62% of existing historical museum specimens demonstrates limited current genetic diversity ( Na  = 2.27, Ar  = 2.24, H e  = 0.43); diversity has declined since the 19th century and even further within the last 30 years, representing declines of ~30% from historical levels ( Na  = 3.36, Ar  = 3.29, H e  = 0.63). Significant differentiation is seen between current and historical samples ( F ST  = 0.156, P  =   0.0315), and the current population exhibits extremely small N e (current N e  = 2.16). There is evidence for both a recent population bottleneck and an earlier bottleneck, with population size already reasonably low by the late 19th century (historical N e  = 1162.96). Individuals in the current population are related at the level of half‐ to full‐siblings between social groups, and full‐siblings or parent–offspring within a social group, suggesting that inbreeding is likely to increase in the future. The species' current reduced genetic diversity must be considered during conservation planning, particularly for expectations of likely population recovery, indicating that intensive, carefully planned management is essential.